1994
DOI: 10.1149/1.2054970
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects and Passivation Studies on Undoped and Ag‐Doped YBa2Cu3 O 7 − x Laser Ablated Thin Films

Abstract: We have examined the chemical stability of undoped and 5 weight percent Ag-doped YBa2Cu3OT_= thin films, both grown in situ by pulsed laser deposition technique. The studies indicate that Ag-doped films are more stable than undoped films. The improved chemical stability of Ag-doped films has been attributed to reduction in the effective area of intergranular regions and the presence of passivating silver clusters around grains. The study has also shown that coating the YBa2Cu307 = film surface with noble metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…While the mechanical strength of the YBCO thin films was not the motivating factor, the primary goal was to obtain an increase in the critical current densities (J c ) of these films. A number of researchers [6][7][8][9][10] have confirmed that the films grown by PLD from these composite targets show enhancement in J c . The existing literature emphasizes the role of Ag in improving the growth characteristics of the films and in providing extra oxygen to the growing film.…”
Section: Introductionmentioning
confidence: 92%
“…While the mechanical strength of the YBCO thin films was not the motivating factor, the primary goal was to obtain an increase in the critical current densities (J c ) of these films. A number of researchers [6][7][8][9][10] have confirmed that the films grown by PLD from these composite targets show enhancement in J c . The existing literature emphasizes the role of Ag in improving the growth characteristics of the films and in providing extra oxygen to the growing film.…”
Section: Introductionmentioning
confidence: 92%